The Influence of Independent Learning Curriculum on The Establishment of Religious Character of MTS Students - Mumun Munawaroh; Yayat Suryatna; Tamsik Udin (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The purpose of this study was to determine the influence of the role of the independent learning curriculum on the formation of the religious character of MTs students. This research uses a qualitative approach with a descriptive method. The data source in this study is words and actions obtained from informants involved in the investigation. Furthermore, documents or other written sources are additional data. As for data collection using observation, interviews, and documentation. To analyze data obtained using continuous observation techniques, data triangulation, data checking, peer discussion and reference adequacy. The results of research findings, data analysis, and discussions that have been carried out can be concluded. The independent learning curriculum can shape students' character in a better direction. This can be seen in the religious feeling of students at MTS, namely the nature of the discipline, respect for teachers, confidence, seriousness, and Islam during the learning process. However, the independent learning curriculum has various obstacles, such as less creative teachers who do not master the independent learning curriculum.